Pengaruh Perceived Value Dan Purchase Attitude Terhadap Purchase Intention Pada Produck Mcdonald’s Pada Saat Melakukan Palestine Washing Dan Dimediasi Oleh Word Of Mouth - Anjani, Nadila; Lidiawati, Lindiawati (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
The research aims to test perceived value, purchase attitude, purchase intention, and word of mouth in McDonald's products that carry out humanitarian programs or so-called Palestine Wasing. The study involved 322 respondents who consumed McDonald's products, and used a questionnaire through google from for data collection. This study uses a quantitative method and the analysis technique uses WarpPLS software. The results of the study showed that perceived value had a significant positive effect on purchase attitude, purchase attitude had a significant positive effect on purchase word of mouth, and word of mouth had a significant positive effect on purchase intention, then purchase attitude had a significant positive effect on purchase intention and then mediated with word of mouth.